2004
DOI: 10.1300/j026v21n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Media Credibility and Informativeness of Direct-to-Consumer Prescription Drug Advertising

Abstract: In this article, we report the results of a study conducted to determine consumer perceptions of the media credibility and informativeness of direct-to-consumer prescription drug advertising (DTC advertising) and to examine how those perceptions are influenced by consumer predispositions and demographic characteristics, especially consumer age. This study specifically surveyed older consumers, who are the most significant market segment for prescription drugs and particularly susceptible and vulnerable to comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…Specifically, we surveyed a randomly selected sample of consumers to measure skepticism toward DTCA and to determine how DTCA skepticism is related to the use and perceived usefulness of different interpersonal and mediated sources of prescription drug information. Though many studies of DTCA have been conducted (e.g., Balazs, Yermolovich, & Zinkhan, 2000;DeLorme, Huh, & Reid, 2007;Deshpande, Menon, Perri, & Zinkhan, 2004;Doucette & Schommer, 1998;Huh, DeLorme, & Reid, 2004a, 2004b, 2005Kim, 2005;Kim & King, 2009;Macias, Pashupati, & Lewis, 2007;Menon, Deshpande, Perri, & Zinkhan, 2002;Williams & Hensel, 1995), only two have reported findings on skepticism toward pharmaceutical advertising, and none have investigated how DTCA skepticism is related to the informational utility of different sources of prescription drug information. The two studies, authored by Diehl et al (2007Diehl et al ( , 2008, are reviewed later.…”
mentioning
confidence: 99%
“…Specifically, we surveyed a randomly selected sample of consumers to measure skepticism toward DTCA and to determine how DTCA skepticism is related to the use and perceived usefulness of different interpersonal and mediated sources of prescription drug information. Though many studies of DTCA have been conducted (e.g., Balazs, Yermolovich, & Zinkhan, 2000;DeLorme, Huh, & Reid, 2007;Deshpande, Menon, Perri, & Zinkhan, 2004;Doucette & Schommer, 1998;Huh, DeLorme, & Reid, 2004a, 2004b, 2005Kim, 2005;Kim & King, 2009;Macias, Pashupati, & Lewis, 2007;Menon, Deshpande, Perri, & Zinkhan, 2002;Williams & Hensel, 1995), only two have reported findings on skepticism toward pharmaceutical advertising, and none have investigated how DTCA skepticism is related to the informational utility of different sources of prescription drug information. The two studies, authored by Diehl et al (2007Diehl et al ( , 2008, are reviewed later.…”
mentioning
confidence: 99%
“…Since different scholars have posed contradictory assertions regarding the direction of the relationship between trust and attitudes (e.g., Grazioli & Jarvenpaa, 2000;Huh et al, 2004a), trust was included among the set of independent variables for the regression on attitude. Indeed, trust was consistently identified as a significant predictor across all three age groups.…”
Section: Factors Related To Trust Attitudes and Behaviormentioning
confidence: 99%
“…DTCA research has often focused on ''older'' adults (DeLorme, Huh, & Reid, 2007;Huh, DeLorme, & Reid, 2004a). Older adults are certainly a significant market segment for advertisers of prescription medicine given their susceptibility to health concerns (Huh et al, 2004a;Foley, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers have consistently expressed a desire for information on indications and drug side effects (Foley and Gross 2000;Tucker and Smith 1987;Woloshin et al 2004;Young et al 2005). In opinion and attitude research, consumers have generally been found to have 'neutral' or 'positive' attitudes to consumer marketing of medicines as a source of information (Alliance for Access to Medical Information (AAMI) 2002; Bell et al 1999a;Beltramini 2006;Gonul et al 2000;Herzenstein et al 2004;Hoek et al 2004;Huh et al 2004a;Huh et al 2004b;Miller and Waller 2004;Murray et al 2004;National Consumers League 2003;Perri and Nelson Jr. 1987;Robinson et al 2004;Vatjanapukka 2004). However exposure to consumer marketing of medicines does not appear to improve the accuracy of consumers' knowledge about drugs (Brodie 2001;Hoek 2007;Kaphingst et al 2005), and consumers generally express skepticism about the quality and credibility of information provided by such marketing and conflicting, diverse or inconsistent attitudes on the benefits and risks posed by it (Alperstein and Peyrot 1993;Foley and Gross 2000;Herzenstein et al 2004;Marinac et al 2004;Miller and Waller 2004;Robinson et al 2004;Young et al 2005b).…”
Section: Introductionmentioning
confidence: 99%